2020
DOI: 10.1002/ejic.201901112
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of Poly‐Yne Carbon Chains and Derivatives with Transition Metal End‐Groups

Abstract: During the last three decades, experimental chemists have forged a plethora of bimetallic molecular wires in which two redox‐active metal termini are linked by a carbon‐rich bridge. Their extensive redox chemistry with multiple, stepwise, one‐electron oxidation processes provide them with some interesting electronic and/or magnetic properties for potential applications. The nature of both the metal end‐groups and the carbon bridge has a significant effect on the redox process, which is of paramount importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 173 publications
0
17
0
Order By: Relevance
“…Metal alkynyl complexes have been an attractive target for both synthetic and material chemists since the pioneering work of Nast and subsequent development in polymerization by Hagihara . Exploration of novel alkynyl complexes based on transition metals has remained topical as evidenced by many comprehensive reviews that have appeared during the ensuing decades. Both the extended conjugation and structural rigidity of metal-oligoynes render them appealing candidates for opto-electronic materials, molecular wires, and active species for molecular devices. It is noteworthy that many of the efforts mentioned above have been based on 4 d and 5 d metals such as Ru, Re, Ir, and Pt, which are rare and precious metals. To transform these interesting properties and functions into technological applications, surrogates based on earth abundant elements are desired.…”
Section: Introductionmentioning
confidence: 99%
“…Metal alkynyl complexes have been an attractive target for both synthetic and material chemists since the pioneering work of Nast and subsequent development in polymerization by Hagihara . Exploration of novel alkynyl complexes based on transition metals has remained topical as evidenced by many comprehensive reviews that have appeared during the ensuing decades. Both the extended conjugation and structural rigidity of metal-oligoynes render them appealing candidates for opto-electronic materials, molecular wires, and active species for molecular devices. It is noteworthy that many of the efforts mentioned above have been based on 4 d and 5 d metals such as Ru, Re, Ir, and Pt, which are rare and precious metals. To transform these interesting properties and functions into technological applications, surrogates based on earth abundant elements are desired.…”
Section: Introductionmentioning
confidence: 99%
“…Following the seminal work on organometallic σ-alkynyl complexes by Nast and co-workers, , considerable attention has been given to the application of these compounds as electronic and optoelectronic materials due to their structural rigidity and high degree of conjugation. In particular, the use of metal alkynyls as the prototypical molecular wires has been investigated by the laboratories of Launay, , Gladysz, , Halet, , Rigaut, and Akita . Compounds exhibiting extraordinary degrees of electron delocalization include those of Fe, Mn, Ru, Ru 2 , and Re. , Though rare, single-molecule conductance has been measured for alkynyl compounds of Pt, , Ru, and Ru 2 , , and functional devices have been fabricated as well. …”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of transition metal alkynyls has evolved extensively since the early study of homoleptic complexes [M­(CCR) m ] n − by Nast and co-workers . In addition to continuous interest in new synthesis and understanding of structures and bonding of metal alkynyls, recent decades have witnessed significant progress in areas such as molecular electronic wires and devices and optoelectronic materials . One of the peculiar attributes of metal alkynyl complexes is the propensity to form an η 2 -adduct of Cu­(I)/Ag­(I) at the acetylenic unit that bonds to the metal center (Chart ), and it has been demonstrated that the η 2 -coordination of Cu­(I) attenuates the electronic coupling between two Ru­(II) centers linked by butadiynyl …”
Section: Introductionmentioning
confidence: 99%